Pengaruh Strategi Pemasaran dan Harga Terhadap Volume Penjualan Produk Kendaraan Sepeda Motor di CV. Cipta Partners Kecamatan Rengat Kabupaten Indragiri Hulu - S, Suprianto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted at CV. Cipta Mitra Usaha District Rengat Indragiri Hulu Regency. The research carried out for approximately 6 (six) months. The purpose of this study was to determine the effect of marketing strategies and prices on sales volumes of motorized vehicle products at CV. Cipta Mitra Usaha Rengat District, Indragiri Hulu Regency. The study was conducted with qualitative methods namely supporting data in the company and quantitative, namely research that describes the Marketing Strategy and Price of Sales Volume of Motorized Vehicle Products on the CV. Cipta Mitra Usaha Rengat District, Indragiri Hulu Regency. By analyzing the data using the instrument test, multiple regression, correlation coefficient and determination, the classical assumption test and hypothesis testing are later assisted by using SPSS version 22 From the results of the study with the regression equation Y = 5.697 + 0.386 X1 + 0.380 X2, a = constant of 5.697 and if the independent variable is considered zero (0) then the constant is 5.697 means that the Sales Volume is 5.697 if X1 (Marketing Strategy) and X2 (Price ) equal to 0 (zero). b1 = Marketing Strategy regression coefficient of 0.386 shows that each increase in Marketing Strategy is one unit and another variable (Price) remains, then there will be an increase in Sales Volume of 0.386. b2 = regression coefficient Price of 0.380 indicates that each increase in price is one unit and another variable (marketing strategy) remains, then there will be an increase in sales volume of 0.380. The correlation coefficient is known that R is 0.796 meaning that it has a strong and unidirectional relationship. and then tested with the coefficient of determination (R2) is 0.456. this shows that (X1) Marketing Strategy and (X2) Prices together can contribute to the variable (Y) Sales Volume of 45.6%. And the remaining 54.4% is influenced by other variables. Hypothesis testing at a significant level = 0.05% where F arithmetic (8.440)> F table (3.11) then Ho is rejected and Ha is accepted. This means that the Marketing Strategy and Price variables together have a significant influence on the Sales Volume of Motorized Vehicle Products on the CV. Cipta Mitra Usaha Rengat District, Indragiri Hulu Regency. Based on the results of the t test obtained the value of t count X1> t table = 2.871> 1.988 so that Ho is rejected and Ha is accepted, which means the independent variable (X1) Marketing Strategy partially has a significant effect on Sales Volume (Y). Furthermore, the value of tcount X2> t table = 3.988> 1.988 so that Ho is rejected and Ha is accepted, which means the independent variable (X2) Price partially has a significant effect on the variable Sales Volume (Y).